Modernization of Social Dialogue through Corporate Social Responsibility in Business Organizations in Indonesia - Andriya Risdwiyanto; Oliviane Oroh; Damir Pada (International Journal of Management Science and Information Technology, 2026)
This study critically examines the modernization of social dialogue through Corporate Social Responsibility (CSR) in Indonesian business organizations. Employing a descriptive qualitative approach, the research utilizes a multiple case study design involving four organizations from the manufacturing, plantation, energy, and financial services sectors. Data collection methods include semi-structured interviews, targeted observations, focus group discussions, and reviews of sustainability reports, CSR documents, regulations, and relevant literature. A total of 24 informants participated, including CSR managers, industrial relations staff, worker representatives, beneficiary communities, local government officials, and civil society organization members. Thematic analysis was conducted to identify patterns related to participation, information transparency, communication equity, complaint resolution, and social outcomes. Findings indicate that CSR initiatives provide substantial benefits through business training, education, health services, financial literacy programs, environmental stewardship, and local economic partnerships. However, stakeholder dialogue remains uneven, as workers and community members are often involved only after program designs are complete. Additionally, complaint mechanisms frequently lack clear response timelines, designated responsible parties, and follow-up reports. While digital channels improve communication efficiency, in-person meetings are still necessary, particularly for groups with limited digital literacy. This research highlights the potential of CSR to enhance social dialogue when stakeholders are actively engaged from the outset.